Responsabilidade socioambiental na produção do artesanato do barro na cidade de Tracunhaém - PE - MENDES, Eduardo Lourenço (2013)
This twork aims to describe the general structures of the production process from mud, identifying the effects of the use of forest biomass (firewood and wood) as input for burning mud energetic about environmental degradation in the town of Tracunhaém, Nourth Forest Zone of Pernambuco - PE in order to understand to what extent the mud artisans take into consideration in their practices, notions about the environmental balance. Sought to verify the practice of craft production of mud facing input use energy less harmful to the environment, beyond the possibility of implementing other sources of energy generation that are not extracted from the original native forest. As a method for data collection, it used primary research through the questionnaires of quantitative and qualitative research as well as literature on modality or secondary sources (books, internet, dissertations, articles, etc..) To understand the means of production, the profile of the mud artisan producers and their perception of the municipality with respect to environmental damage that the use of forest biomass may cause to the environment. Sustainable development is currently a topic of great relevance to all nations, and the concept of environmental responsibility relevant to achieve a global stage in allowing the present generation to act responsibly to meet present needs without compromising the opportunity to meet satisfation needs of future generations. Thus, the practice of environmental responsibility must somehow have bounce on mud handiwork of the town analized Based on the data obtained, it was found that the 48 parts manufacturing workshops mud use 55 ovens, being 54 wood burning and only one by gas, which eventually leads to excessive consumption of firewood, representative factor of potential threats to the environment, if not the short, the medium and long term. This study analyzed the situation and sought to measure the environmental perception of artisans, as well as its ability to forward solutions to this problem that, ultimately, affects everyone. The study concludes that the artisans have a vision of environmental concerns, but alone can not intervene in the process in order to give more durable solution to the problem. The solutions would have to count on the support of local government, combining efforts with state and federal powers to propose alternatives in the form of appropriate public policies, such as the reforestation of specific areas in the state of Pernambuco, if you want to stop the advance of deforestation in the Atlantic Forest, as well as deforestation in other regions of the state such as the wilderness (where craftsmen also seek feedstocks for their activities). Thus, only a policy of environmental responsibility involving public and private actors could effectively contribute to reduce the problems caused to the environment by developing this craft activity in the study area.